Owning the Water - Rodwell, John (Anglican theological review, 2018)
The article presents a sermon given by ecologist and priest John Rodwell on March 12, 2017 at St. Paul's Cathedral in London, England. topics include the spiritual significance of water, the notion of ownership in theological perspective in relation to greed, and the idea of justice in relation to water rights.